The key role of sphingolipid metabolism in cancer: New therapeutic targets, diagnostic and prognostic values, and anti-tumor immunotherapy resistance - Li, Run-Ze; Wang, Xuan-Run; Wang, Jian; Xie, Chun; Wang, Xing-Xia; Pan, Hu-Dan; Meng, Wei-Yu; Liang, Tu-Liang; Li, Jia-Xin; Yan, Pei-Yu; Wu, Qi-Biao; Liu, Liang; et al. (Frontiers in Oncology, 2022)
Biologically active sphingolipids are closely related to the growth, differentiation, aging, and apoptosis of cancer cells. Some sphingolipids, such as ceramides, are favorable metabolites in the sphingolipid metabolic pathway, usually mediating antiproliferative responses, through inhibiting cancer cell growth and migration, as well as inducing autophagy and apoptosis. However, other sphingolipids, such as S1P, play the opposite role, which induces cancer cell transformation, migration and growth and promotes drug resistance. There are also other sphingolipids, as well as enzymes, played potentially critical roles in cancer physiology and therapeutics. This review aimed to explore the important roles of sphingolipid metabolism in cancer. In this article, we summarized the role and value of sphingolipid metabolism in cancer, including the distribution of sphingolipids, the functions, and their relevance to cancer diagnosis and prognosis. We also summarized the known and potential antitumor targets present in sphingolipid metabolism, analyzed the correlation between sphingolipid metabolism and tumor immunity, and summarize the antitumor effects of natural compounds based on sphingolipids. Through the analysis and summary of sphingolipid antitumor therapeutic targets and immune correlation, we aim to provide ideas for the development of new antitumor drugs, exploration of new therapeutic means for tumors, and study of immunotherapy resistance mechanisms.